2022
DOI: 10.1136/bmjopen-2021-054709
|View full text |Cite
|
Sign up to set email alerts
|

RetroBRACE: clinical, socioeconomic and functional–biomechanical outcomes 2 years after ACL repair and InternalBrace augmentation in comparison to ACL reconstruction and healthy controls—experimental protocol of a non-randomised single-centre comparative study

Abstract: IntroductionDespite good clinical outcomes reported in the literature, to date, scientific evidence for the functional and biomechanical benefit of primary anterior cruciate ligament (ACL) repair with augmentation is scarce. We present an experimental protocol for a detailed multimodal (clinical, socioeconomic, functional and biomechanical) comparative study in patients after primary ACL repair and InternalBrace augmentation, patients after ACL reconstruction and healthy controls.Methods and analysisIn this no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Much more attention has been paid to proprioception related to rehabilitation and gait than to the surgery associated with the injury. To improve long-term function, physicians have established rehabilitation programs for patients that focus not only on range of motion and strengthening exercises but also on proprioceptive and neuromuscular control drills [ 20 , 32 – 34 ]. Müller et al showed that a functional neuromuscular training program was more effective than traditional muscle strength rehabilitation programs in improving function [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much more attention has been paid to proprioception related to rehabilitation and gait than to the surgery associated with the injury. To improve long-term function, physicians have established rehabilitation programs for patients that focus not only on range of motion and strengthening exercises but also on proprioceptive and neuromuscular control drills [ 20 , 32 – 34 ]. Müller et al showed that a functional neuromuscular training program was more effective than traditional muscle strength rehabilitation programs in improving function [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…To improve long-term function, physicians have established rehabilitation programs for patients that focus not only on range of motion and strengthening exercises but also on proprioceptive and neuromuscular control drills [ 20 , 32 – 34 ]. Müller et al showed that a functional neuromuscular training program was more effective than traditional muscle strength rehabilitation programs in improving function [ 34 ]. The results from all these aforementioned studies indicated that appropriate proprioception exercises would be expected to achieve significant improvements in knee proprioception and function in patients following ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…This study is a substudy of a larger non-randomised comparative umbrella study with retrospective data collection [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The detailed study protocol including all performed analyses has been previously published. 34 After careful evaluation of inclusion and exclusion criteria (Table 1), the following groups were included in our study: ACL-IB: consecutive patients 2 years after primary ACL repair and ligament augmentation operated at our institution and checked for inclusion and exclusion criteria (Table 1 and Figure 1) (n = 29). ACL-R: patients 2 years after ACL-R with autologous hamstring grafts were selected on the basis of sex and age from all patients treated in our clinic to obtain a sex-and age-matched comparison group (n = 27).…”
Section: Patients and Controlsmentioning
confidence: 99%